Effects of relative humidity on heterogeneous reaction of SO2 with CaCO3 particles and formation of CaSO4·2H2O crystal as secondary aerosol. (1st January 2022) - Yue, Yang; Cheng, Jingru; Lee, Kang Soo; Stocker, Roman; He, Xu; Yao, Maosheng; Wang, Jing
Abstract: Haze related air pollution has become one of major environmental concerns in some Asian countries. Sulfate is a main component of ambient particulate matter (PM) in the urban environment during haze episodes. Among the pollutants, sulfur dioxide (SO2 ) is an important precursor of sulfate and new atmospheric particle formation. However, under different atmospheric conditions its underlying formation mechanisms are not clearly elucidated. In the current work, we collected ambient PM in two cities: Zurich (Switzerland) and Beijing (China). The PM morphology and the composition were investigated by scanning electron microscopy, energy dispersive X-Ray spectroscopy and Raman micro-spectroscopy. In addition, a series of lab controlled experiments were also performed to study the SO2 reaction with CaCO3 aerosol. We found different types of CaSO4 ·2H2 O crystals in the Chinese urban samples, with clearly different compositions than those from Zurich. The experimental data showed that the relative humidity played a significant role on the new CaSO4 ·2H2 O crystal formation including its size, morphology and composition. Relative humidity (RH) above 80% can significantly promote SO2 oxidation on the CaCO3 particles and form the CaSO4 ·2H2 O crystals. In contrast, at relative humidity below 40%, only few CaCO3 particles can be converted to CaSO4 particles. The results of this study facilitate the understanding of secondary inorganic aerosol formation by the reaction of CaCO3 particles with SO2 with different RHs in different city environments, and provide useful information for air pollution control. Highlights: Different types of CaSO4 ·2H2 O crystals were observed in some urban ambient particulate matter samples. Lab controlled experiments indicated that relative humidity played a significant role in CaSO4 ·2H2 O crystals formation. The study provides useful information to understand the secondary inorganic aerosol formation and air pollution control.